IFPRI's 2019 Global Food Policy Report Launch: Global Context of Rural Revitalization (Dhaka, Bangladesh) - Fan, Shenggen (2019)
IFPRI's Director General Dr. Shenggen Fan presented on the global context of rural revitalization at the 2019 Global Food Policy Report Launch in Dhaka, Bangladesh.